2012
DOI: 10.1186/1472-6920-12-81
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions and attitudes about family practice: a qualitative research synthesis

Abstract: BackgroundDuring the last decade medical students from most Western countries have shown little interest in family practice. Understanding the factors that influence medical students to choose family medicine is crucial.ObjectiveTo systematically review and synthesize published evidence about medical students’ attitudes and perceptions towards family practice.MethodsA qualitative systematic review. The literature search was undertaken in July 2010 in PubMed, EMBASE, Cumulative Index to Nursing and Allied Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 13 publications
4
61
2
Order By: Relevance
“…It has been found that medical students' perception of a speciality affects their career choice (SelvaOlid et al 2012, Tanser et al 2000. Their career choice can, however, be influenced if their perception about the speciality is altered (Laffey et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that medical students' perception of a speciality affects their career choice (SelvaOlid et al 2012, Tanser et al 2000. Their career choice can, however, be influenced if their perception about the speciality is altered (Laffey et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, it was often expected by students and was obtained by those GPs who managed to work shorter or flexible hours [23, 24, 32, 34, 35, 43, 44]. …”
Section: Discussionmentioning
confidence: 64%
“…Many studies have been conducted around the world in recent years to understand the factors that might more successfully promote general practice as a satisfying and rewarding medical career [61-66]. Although there is some variability, general practice (and family) medicine is often reported in this literature to hold lower levels of interest and prestige in the eyes of medical students than the other speciality fields [67]. Particular barriers compound these more generalised concerns about the image of general practice; for example, a recent survey of Australian general practice trainees identified increasing bureaucracy, workforce shortages, and poor remuneration as potential deterrents to a future career in general practice [68].…”
Section: Discussionmentioning
confidence: 99%
“…These accounts provide a counter perspective to the research literature which has consistently reported that medical students view general practice as offering insufficient ‘scientific-technical interest’ [63] or ‘intellectual content’ [71]. For example, a qualitative synthesis of the literature on choosing general practice reported a recurrent belief that general practice was less intellectually challenging than other areas of medicine, tending to treat only ‘common disease’ [67]. The evidence that our participants achieved great professional satisfaction in acquiring particular and additional forms of expert knowledge on the management of HIV infection challenges the perception that general practitioners and other primary care physicians manage the least exciting aspects of medical work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation